Civil Society Mobilizations Shaping Landscape in Genoa and Girona Areas: Results and Lessons Learnt from the Savingscapes Project - Ilaria Delponte; Valentina Costa; Sergi Nuss Girona; Joan Vicente Rufi (Land, 2023)
This paper deals with the results of the “SavingScapes” research project, where Girona (SP) and Genoa (IT) areas were chosen as case studies to assess the role and relevance of civil society in landscape alteration and conservation. These contexts share many features which led to similar transformative pressures and consequent deeply rooted place attachment clashing in the form of social mobilizations. Nevertheless, the civil society approach and actions proved profoundly different. Hence, there is a need to define a shared methodology to make them comparable. The authors define seven categories, ranging from defeat to prefigurative politics, to assess local mobilization in terms of territorial impacts.